Psychometric evaluation and tests of validity of the Medical Outcomes Study 12-item Sleep Scale (MOS sleep) - Allen, Richard P.; Kosinski, Mark; Hill-Zabala, Christina E.; Calloway, Michael O. (Sleep medicine, 2009)
To validate the psychometric properties of the Medical Outcomes Study (MOS) Sleep Scale in subjects with restless legs syndrome (RLS). Data from a clinical trial program involving two Phase III, double-blind, placebo-controlled trials of ropinirole in subjects with moderate-to-severe primary RLS were analyzed. Subjects were assessed on the MOS Sleep Scale at baseline, Weeks 8 and 12. The baseline validation population included 551 subjects on which full longitudinal data are available. Psychometric assessment of four MOS sleep domains revealed satisfactory item convergent validity ( r > 0.40) for most items. All domain items in both trials surpassed the standard for item discriminant validity, with no significant floor or ceiling effects. The MOS sleep domain scores showed good internal consistency reliability. Concurrent validity ( r = 0.40) was exceeded in correlations between the RLS overall quality-of-life score and sleep problems index II. The clinical validity of the MOS Sleep Scale was demonstrated against self-reported RLS symptoms and clinician-determined severity; changes in MOS Sleep Scale were responsive to improvements in RLS severity, as measured by the Clinical Global Impression-Improvement and Severity-of-Illness scales. The MOS Sleep Scale is a reliable, valid tool for assessing changes in the sleep of subjects with moderate-to-severe primary RLS. The somnolence domain failed to relate to clinical severity of RLS, indicating a possible sleep–wake relationship unique to RLS. Use of this scale to evaluate other conditions causing sleep disturbance is supported.